O conceito de projeto e a implementação de novos sistemas-produto - Schüler, Gabriel Kauffmann (Universidade do Vale do Rio dos Sinos, 2012)
Design nowadays is developing its strategic placement for organizational innovation, bringing a new orientation from where to generate value. Strategic Design proposes a projectual method that proceds from concept development to the implemented solutions. This path is explored in this study in order to clear the concepts' charactheristics as well as the difficulties and standards for its implementation. Three case studies have been made with organizations that proposed to develop Strategic Design projects. In this studies a number os documents were raised and interviews with a manager and a design leader in each one of them. The results point to a series of basic charactheristics of the concepts and relevant topics on the implementation process of strategic design projects
Keywords: Design estratégico; Processo de projeto; Conceito de projeto; Gestão da inovação; Implementação; Strategic design; Project process; Design concept; Innovation management; Implementation; ACCNPQ::Ciências Sociais Aplicadas::Desenho Industrial